(untitled) (MAUSAM, 2005)
Mass density fluctuations of CO2 and water vapor were measured at 5 m above ground level (agl) on a 9 m high micrometeorological tower in the premises of the National Centre for Antarctic and Ocean Research (NCAOR) Vasco da Gama, Goa, as a part of the Arabian Sea Monsoon Experiment (ARMEX). Open path Infra Red (IR) Hygrometer (LI – 7500) was used to collect samples at a rate of 10 per second. Hourly averaged values of CO2 and water vapor were used to study the diurnal variation for 3 days every month in ARMEX phase-I (June-September 2002) and phase-II (March, April, May, June 2003).